3D printing of NiZn ferrite architectures with high magnetic performance for efficient magnetic separation. Issue 4 (April 2022) - Wei, Xiangxia; Pan, Yalei; Chen, Zhangwei
Abstract: Magnetic materials with desired architectures and high performance have become increasingly important for applications. In this work, NiZn ferrites with mesh structures have been successfully fabricated from preliminary precursors by three-dimensional (3D) printing accompanied by the solid-state reaction. The influence of compositions on structural and magnetic properties of NiZn ferrites were systematically investigated. It was obvious that the saturation magnetization was significantly enhanced to 77 emu/g for NiZn ferrites with a zinc concentration of 0.4, which was a much higher value compared to Ni ferrites. This is attributed not only to the well-known cationic distribution, but also to the grain growth with extraordinarily high crystallinity. Consequently, NiZn ferrites with intricate mesh structures were utilized for magnetic separation, and the distributions of magnetic flux density were simulated. Overall, the fabrication of NiZn ferrites by 3D printing is attractive for scaled-up applications, and also paves the promising avenue for magnetic separation.